Faktor Faktor Determinant Pertumbuhan Ekonomi Regional Pada Masa Pandemi Di Jawa Tengah - Kartika Widyasari; Novi Dirgantari; Sri Wahyuni; Hardiyanto Wibowo (Politeknik Ganesha Medan, 2023)
Due to the covid-19 pandemic, which is assumed to be equivalent to the economic crisis, regions in Central Java are one of the regions that are economically highly affected. This is evidenced by the decline in GRDP to -2.65 in the mid-May 2021 period. This research tries to answer the gap between the results of previous research on the variables of local own-source revenue, capital expenditure, unsuspent funds and budget refocusing on regional economic growth. The purpose of this study is to empirically examine the impact of local own-source revenue, capital expenditure, unsuspent funds (SiLPA) and budget refocusing on regional economic growth in central Java regions and cities in 2019-2021. The research method used is quantitative with secondary data and multiple linear regression as the data analysis technique. The data collection technique in this study used a saturated sampling technique with a sample of 35 districts and cities in Central Java. The results showed that local own-source revenue (PAD), capital expenditure and unsuspent funds have a positive effects on regional economic growth. Meanwhile, budget refocusing have no effect on regional economic growth.